2001
DOI: 10.1378/chest.120.2.617
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin-Induced Pneumonitis

Abstract: The cytotoxic agent bleomycin is feared for its induction of sometimes fatal pulmonary toxicity, also known as bleomycin-induced pneumonitis (BIP). The central event in the development of BIP is endothelial damage of the lung vasculature due to bleomycin-induced cytokines and free radicals. Ultimately, BIP can progress in lung fibrosis. The diagnosis is established by a combination of clinical symptoms, radiographic alterations, and pulmonary function test results, while other disorders resembling BIP have to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
396
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(410 citation statements)
references
References 76 publications
3
396
0
11
Order By: Relevance
“…Generation of the ROS in the lung tissue results in DNA injury, lipid peroxidation, alteration in lung prostaglandin synthesis and degradation, and an increase in lung collagen synthesis. As a result of the injury, inflammation and cytokine dysregulation occur after BLM administration, fibroblasts are activated, and collagen production is stimulated, while collagen degradation is inhibited (Sleijfer 2001). In addition, several studies have demonstrated that bleomycin administration in rats decreases the antioxidative capacity, while increasing oxidative stress in the lung tissue (Mata et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Generation of the ROS in the lung tissue results in DNA injury, lipid peroxidation, alteration in lung prostaglandin synthesis and degradation, and an increase in lung collagen synthesis. As a result of the injury, inflammation and cytokine dysregulation occur after BLM administration, fibroblasts are activated, and collagen production is stimulated, while collagen degradation is inhibited (Sleijfer 2001). In addition, several studies have demonstrated that bleomycin administration in rats decreases the antioxidative capacity, while increasing oxidative stress in the lung tissue (Mata et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…3 Specifically, bleomycin is commonly associated with pulmonary toxicity and it is likely that the endothelium is the initial site of damage. 5 This chemotherapeutic drug is a DNA scission agent whose mechanism likely involves intercalation and the release of oxidants that cause damage to the DNA template during replication. This may initiate a cascade of inflammatory events culminating in macrophage infiltration and epithelial injury, characterized by the appearance of dysplastic alveolar epithelial cells.…”
mentioning
confidence: 99%
“…7 Though the exact mechanism by which bleomycin results in lung injury is unclear, free-radicalinduced oxidation is considered the primary mechanism. 8 The relative deficiency of the bleomycin-inactivating en- Fig. 1.…”
Section: Discussionmentioning
confidence: 99%